Faktor-Faktor yang Mempengaruhi Niat Mahasiswa untuk Berwirausaha: Aplikasi Theory of Planned Behavior - Anik Sri Widawati; Budi Astuti (Sinergi: Kajian Bisnis dan Manajemen, 2012)
This study is a replication of research by Shook and Bratianu (2010). Variables that affect student intentions for entrepeneurship in this study are specific desirabilities, subjective norms, self-efficacy, perceived desirability and the perceived feasibility. Sampling was purposive sampling method. The number of samples of this study as much as 306 students. This study uses path analysis model with three channels equation. The result of path analysis in this study are as follows: 1) specifis desirabilities, subjective norms, and self-efficacy has positive and significant impact on entrepreneurial intentions, 2) perceived desirability of modifying the effect of specific desirabilities on intent entrepreneurship, 3) perceived feasibility to modify the effect of self-efficacy on entrepreneurship intentions. Desirabilities specific influence on entrepreneurial intentions became stronger after the mediation by the perceived desirability. Similarly, the influence of self-efficacy on entrepreneurial intentions became stronger after the mediation by the perceived feasibility. While the variables that have the most dominant influence in affecting entrepreneurial intentions are perceived desirability. The conclusion of this study is that the entrepreneurial intentions of students in assesment criteria very well. Therefore, entrepreneurship courses should be made as a compulsory subject for all courses.Keywords:     specific desirabilities, subjective norms, self-efficacy, perceived desirability and the perceived feasibility and entrepreneurship intentions.